Harnessing Dendritic Cells for Poly (D,L-lactide-co-glycolide) Microspheres (PLGA MS)—Mediated Anti-tumor Therapy - Koerner, Julia; Horvath, Dennis; Groettrup, Marcus (Frontiers in Immunology, 2019)
With emerging success in fighting off cancer, chronic infections and autoimmune diseases, immunotherapy has become a promising therapeutic approach compared to conventional therapies such as surgery, chemotherapy, radiation therapy or immunosuppressive medication. Despite the advancement of monoclonal antibody therapy against immune checkpoints, the development of safe and efficient cancer vaccine formulations still remains a pressing medical need. Anti-tumor immunotherapy requires the induction of antigen-specific CD8+ cytotoxic T lymphocyte (CTL) responses which recognize and specifically destroy tumor cells. Due to the crucial role of dendritic cells (DCs) in initiating anti-tumor immunity, targeting tumor antigens to DCs has become auspicious in modern vaccine research. Over the last two decades, micron- or nanometer-sized particulate delivery systems encapsulating tumor antigens and immunostimulatory molecules into biodegradable polymers have shown great promise for the induction of potent, specific and long-lasting anti-tumor responses in vivo. Enhanced vaccine efficiency of the polymeric micro/nanoparticles has been attributed to controlled and continuous release of encapsulated antigens, efficient targeting of antigen presenting cells (APCs) such as DCs and subsequent induction of CTL immunity. Poly (D, L-lactide-co-glycolide) (PLGA), as one of these polymers, has been extensively studied for the design and development of particulate antigen delivery systems in cancer therapy. This review provides an overview of the current state of research on the application of PLGA microspheres (PLGA MS) as anti-tumor cancer vaccines in activating and potentiating immune responses attempting to highlight their potential in the development of cancer therapeutics.